1 Aslah personal financing-I and customer satisfaction: a case study of Bank Rakyat, Masai / Nur Farahin Rashid - Rashid, Nur Farahin (2011)
Customer satisfaction is an essential factor in realizing positive outcomes such as customer loyalty, customer retention and ultimately, profitability. Despite its importance, the attempt to understand what makes customers satisfied remains a difficult task and this pose key challenge and is a critical management issue today. For these reasons, customer satisfaction is the primary focus of this study. The data for this research was collected from 40 customers of Bank Rakyat Masai who applied and successfully obtained a personal loan in Bank Rakyat Masai where majority of them are from the government sector and private sector. The main objective of this report is to identify the factors that influence the level of customer satisfaction when choosing 1-Aslah Personal Financing. This study is initiated to look into the process of disbursing 1-Aslah personal financing and how it affects the customer level of satisfaction. There are many levels of satisfactions whether from the services management, public image of that particular bank, product that provided by the bank and others. In this study, the researcher collects the information about customer satisfaction from interview, observation, website and secondary data such as journal, article, annual report and also text book. This study will help Bank Rakyat Masai to identify their weakness in order to achieve the level of customer satisfaction towards 1-Aslah Personal Financing. The study utilized questionnaires as the instrument for collecting data. Questionnaires have been distributed to 40 respondents. The data collected was analyzed using techniques of frequency distributions, reliability analysis and also Cronbach’s Alpha of Statistical Package for Social Sciences (SPSS) version 16.0. The results were presented in frequency tables and charts. The study was found that majority of the customers are satisfied with the services quality of BRM staffs and also quality of 1-Aslah Personal Financing-I products. In conclusion, some suggestion and strategies have been made to minimize problem that occur in Bank Rakyat Masai. This is important because it will help Bank Rakyat Masai to improve their quality service and it will affect the level of customer satisfaction towards Bank Rakyat Masai product and service.